2021
DOI: 10.1021/acscatal.1c01294
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Inspection of M1/PMA Single-Atom Electrocatalyst: Ultra-High Performance for Water Splitting (HER/OER) and Oxygen Reduction Reactions (OER)

Abstract: Developing a cost-effective and highly efficient electrocatalyst with superior catalytic activity is crucial for clean and green water splitting, including the hydrogen evolution reaction (HER), the oxygen evolution reaction (OER), and the oxygen reduction reaction (ORR). The single-atom catalyst (SAC) is a breakthrough in industrial catalysis because of the advantages of maximum metal atom utilization, single active sites, strong metal−support interactions, and great potential to accomplish high catalytic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 72 publications
0
74
0
Order By: Relevance
“…It is found that the TMs prefer to anchor to the 4-H site of Na 4 SiMo 12 , which is consistent with the previous studies. 34,36,52–55 Based on the above analysis, the calculation model of TM@Na 4 SiMo 12 was confirmed and is shown in Fig. 3a, in which the TMs are anchored on the POM 4-H site.…”
Section: Resultsmentioning
confidence: 80%
“…It is found that the TMs prefer to anchor to the 4-H site of Na 4 SiMo 12 , which is consistent with the previous studies. 34,36,52–55 Based on the above analysis, the calculation model of TM@Na 4 SiMo 12 was confirmed and is shown in Fig. 3a, in which the TMs are anchored on the POM 4-H site.…”
Section: Resultsmentioning
confidence: 80%
“…In this work, the PMA cluster was selected as the support to study single transition metal atom (TM= Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, W, Re, Os, Ir, Pt, and Au) catalysts for the eNRR, since PMA has appeared to be an attractive support to anchor transition metal atoms. 78 It is notable that the Keggin-type PMA cluster is built by 12 MoO 6 octahedra that connect their corners or edges to a central PO 4 tetrahedron, and its fully optimized structure is shown in Fig. S1 †.…”
Section: Resultsmentioning
confidence: 99%
“…According to η OER for FeP4 (0.73 V), NiP4 (0.84 V), CuP4 (2.93 V), PdP4 (0.75 V), AgP4 (1.44 V), PtP4 (0.56 V) and AuP4 (0.67 V), these TMP4 catalysts can also be reported inappropriate for the OER. Remarkably, the CoP4 and RhP4 catalysts exhibit outstanding OER catalytic performance, with the η OER of 0.32 and 0.50 V, respectively, which are better than or comparable to those of Pt1/PMA (0.49 V) [55], RuO2 (0.42 V) [56], ZnN4-edge (0.63 V) [57], and the commonly used IrO2 (0.56 V) [56] catalysts. Thus, the CoP4 and RhP4 can assist as the high active catalysts for the OER.…”
Section: Bifunctional Orr/oer Catalytic Activities Of Tmp4mentioning
confidence: 95%
“…(1.75 V), OsP4 (1.72 V) and IrP4 (0.80 V) indicate that the high enough input energies are required for the effective OER catalytic performance. Additionally, previous study [55] has reported that the robust binding interaction and excess energy go against the elimination of related OER intermediates, impeding the active sites and poisoning the catalysts. Hence, the aforementioned TMP4 catalysts are not regarded as the available catalysts for OER.…”
Section: Bifunctional Orr/oer Catalytic Activities Of Tmp4mentioning
confidence: 96%